Abu Mansur Al-Thaʿālibī and his Anthology "Kanz Al-Kuttab" - Hulkar Muminjonovna, Sulaymonova (International Journal of Psychosocial Rehabilitation, 2020)
The famous scientist, poet, and writer Abu Mansur al-Thaʿālibī (961-1038) is the author of more than 100 works. They are devoted to linguistics, literature, rhetoric, and other branches of philological science, as well as history and Islamic law (fiqh). This article provides information on the structure of the structure and features of the work “Kanz al-kuttab” by Abu Mansur al-Thaʿālibī. The manuscript of this work, which is kept in Tashkent, has been studied from the point of view of literary source study.